Socio-economic Determinants of Coastal Fisherman: Evidence from Indonesia - Fatimah, Jeanny Maria; Pulubuhu, Arianto, Dwia Aries Tina (International Journal of Psychosocial Rehabilitation, 2020)
Socio-economic determinants are still become serious issue. This study aims to provide information about socio-economics aspects of coastal fisherman. The research used constructivism paradigm using descriptive qualitative and quantitative methods. The results show that socio-economic determinants of coastal fisherman are low-income category, low level of education (primary school), working age is still productive, less diverse of technology utilization and are still strongly depending on the ‘tengkulak’ (middleman). This implies that the government needs to concern on these determinants in order to increase coastal fisherman welfare.